Dittrichia viscosa (Asterales: Asteraceae) as an Arthropod Reservoir in Olive Groves - Alcalá Herrera, Rafael; Castro-Rodríguez, Juan; Fernández-Sierra, María Luisa; Campos, Mercedes (Frontiers in Sustainable Food Systems, 2019)
Non-crop cultivated plants can provide agriculture with ecosystem services such as biological pest control and, a sound knowledge of the relationships between these plants and arthropod communities is important. Given its entomophilous characteristics, Dittrichia viscosa, a plant commonly found in the Mediterranean region, could potentially be used in integrated pest management systems. The aim of this study is to investigate arthropofauna associated with D. viscosa in olive groves during its preflowering, flowering and postflowering stages and to determine the possible relationships between different groups of arthropods. Using vacuum-sampling, the study was carried out on D. viscosa plants bordering and inside olive groves. The plants produced new leaves in April and flowered between August and October. Miridae, Aphididae, Hymenoptera parasitoids, Formicidae, Araneae and Aleyrodidae were the most abundant groups of arthropods collected during the preflowering and flowering stages. Plant phenology differentially influenced the arthropod populations of the different groups, with the Aleyrodidae family found to be more abundant during the preflowering stage, while Hymenoptera parasitoids were more numerous during the flowering stage. During the postflowering stage, the number of arthropods captured was very low. Numerous correlations between and within the different functional groups were observed throughout the life cycle of D. viscosa. Our results clearly show that D. viscosa plants in olive groves have great potential as a reservoir of different predators and Hymenoptera parasitoids and that these olive groves were not attacked by any D. viscosa-related phytophages.